Biomethanation of syngas at high CO concentration in a continuous mode. (February 2022) - Li, Yeqing; Liu, Yinjun; Wang, Ximeng; Luo, Sen; Su, Dongfang; Jiang, Hao; Zhou, Hongjun; Pan, Junting; Feng, Lu
Graphical abstract: Highlights: Syngas biomethanation was completed under higher CO concentration (40%) and higher processing capacity (12.6 m 3 /m 3 /d). Biomethanation with syngas as the only carbon source can operate continuously and stably for a long time. The syngas biomethanation path is shown by combination of theoretical calculation and practice. Abstract: Syngas from pyrolysis/gasification process is a mixture of CO, CO2 and H2, which could be converted to CH4, so called syngas biomethanation. Its development is obstructed due to the low productivity and CO inhibition. The aim of this study was to demonstrate the feasibility of using syngas as the only carbon source containing high CO concentration (40%) for biomethanation. Lab-scale thermophilic bioreactor inoculated with anaerobic sludge was operated continuously for over 900 h and the shift of microbial structure were investigated. Results showed that thermophilic condition was suitable for syngas biomethanation and the microbes could adapt to high CO concentration. Higher processing capacity of 12.6 m 3 /m 3 /d was found and volumetric methane yield of 2.97 m 3 /m 3 /d was observed. These findings could strengthen the theoretical basis of syngas biomethanation and support its industrialization in the future.